PENDIDIKAN KESEHATAN DAPAT MEMPENGARUHI PENGETAHUAN, SIKAP PRA REMAJA MENGHADAPI MENARCHE - Mualifah, Laily; Pangastuti, Nuring; Purwanta, Purwanta (Journal of Holistic Nursing Science, 2019)
Menarche and menstruation is a physiological process that can cause physical discomfort, emotional and anxiety. SDN in Cluster 3 and 4 Districts Nanggulan there were 10 grade 5 and 6 are not yet menarche say not know about menarche and menstruation and not knowing what to do when menstruation occurs. This happens because there is no health education about menstruation health in the scope of elementary school. Objective: To determine the effectiveness of health education with group discussion and lecture method to the knowledge, attitudes pre teens to face of menarche. Methods: This study is quasy-experiment with approaches pre test-post test control group design. Subjects were 5th and 6th grade students of elementary school at Cluster 3 and 4 Districts Nanggulan Kulon Progo with as many as 111 (discussion method,n = 55 and lecture method,n = 56) who met the inclusion criteria. The instrument used questionnaire. The sampling technique purposive sampling. Statistical test using Friedman test, Wilcoxon test and Mann-Whitney Test. Results: Scores of knowledge and attitudes before and after treatment there were significant differences in group discussions and lectures with the p=0,00 (p <0.05). Increased knowledge and attitude scores in both groups were significantly different at p=0,00 dan p=0,02 (p <0.05). The increase in effective knowledge and attitude scores on the method of discussion on the first day, the third and fourteenth after health education. Conclusion: Health education with discussion method is more effective than lecture group in increasing knowledge and changing attitudes in the pra-puberty facing menarche. Keywords: health education, group discussion method, menarche